Avaliação do método Pilates no alinhamento postural em adolescentes portadores de escoliose, por meio da eletromiografia e da simetrografia - Strasse, Wally auf der (2016)
Scoliosis is considered the fifth most common pathology in development during adolescence. And in Brazil the prevalence of this disease ranges from 2% to 4% in adolescents aged 10-16 years old. The Pilates method can be considered as an alternative to conservative treatment of this postural deviation. The aim of this study was to evaluate the Pilates method in the postural alignment of adolescents with scoliosis through electromyography and symmetrography. An exploratory study was conducted from February to April 2015, with 22 12 to 18 year old male and female adolescents who had the scoliosis postural deviation, physically active, without experience in resistance training of Pilates and who had not performed orthopedic corrective surgery on the spine and not been diagnosed with rheumatic disease. Both surveyed volunteers and their parents filled informed consents. The investigated teenagers initially underwent anthropometric measurements, body fat percentage, body symmetry, Adams test and electromyographic assessment in trapezius, erector spinal, obliques and rectus abdominis, in a seated position balancing a book on their heads processed in the time (EMGAmp ) and spectral domains (EMGFmed). After that they were submitted to 24 sessions with two weekly appointments of a treatment protocol consisting of Pilates exercises. After the application of this protocol, they were again subjected to initial assessments. Data were analyzed by ANOVA and processed by using the statistical software R version 3.2.0. and McNemar test. Results regarding scoliosis showed that nine adolescents improved postural alignment (40.9%) (p = 0.001) and there was also an improvement in the shortening of the trapezius (p = 0.031) and asymmetrical shoulders (p = 0.001). Concerning the EMGAmp in right postural scoliosis (EPD), there was a significant difference between before and after (p = 0.081) and also between muscles (p = 0.031); in the right thoracic scoliosis (ETD) there was a difference between before and after (p≈0), the right side of the left (p = 0:04) and between muscles (p≈0); in the left thoracic scoliosis (ETE) and convex left thoracolumbar scoliosis (ETLDC) differences between before and after (p≈0) and between muscles (p≈0) were found. Concerning the EMGFmed in the EPD there was a difference between before and after (p≈0) and between muscles (p = 0.001); in the ETD there was a difference between before and after (p≈0) and between muscles (p = 0.007); in ETE and ETLDC there was a difference only between before and after (p≈0); in ETLE there was a difference between before and after (p = 0.007). In all cases of scoliosis studied here, there was an increase of EMGFmed notably in the OBLI and RA muscles. There were statistical differences in height variables (p = 0.003) and increased flexibility (p = 0.000). One can conclude that the results point to the importance of Pilates exercises as a form of conservative treatment of scoliosis, causing changes in the pattern of neuromuscular activation. However, in relation to the therapeutic application time relative to postural alignment, it is suggested to develop it in longer periods.